CREATIVITY AS A COMPONENT OF HIGHER EDUCATION PROFESSIONAL TRAINING: creativity, creative competence, personal approach, subject-subject interaction, methods of creativity development, applicants for higher education - Kokarieva, Anzhelika (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The study urgency is due to the fact that today the higher education system is intensively transitioning to new educational standards, implementing an individual personality-oriented approach in the educational environment, the priority tasks include educating creative individuals capable of creative activity in various life spheres. its competitive in the labor market worldwide. Effective communication, mobility and creativity are the main requirements of modern market for graduates of higher education institutions. Therefore, nowadays, HEI teachers should organize the educational environment creatively, improve and modernize classical teaching methods, develop creativity and critical thinking of applicants for higher education. The purpose of the article is to substantiate the importance of developing creativity in the training of applicants for higher education. The activity of teachers is aimed primarily at deepening the cognitive interest of applicants for higher education, their involvement in creative independent activities, ensuring a high level of training of future professionals, the development of their competitiveness and the formation of creative activity. methods that we used are: theoretical analysis, synthesis - to characterize the key research concepts ; analysis of documents - to study scientific sources, regulations, legislation; systematization and generalization - to formulate conclusions and recommendations that allowed to clarify the creativity benefits in the higher education training; empirical (interviews, questionnaires, observation of the educational process). The research results showed that this problems solution is relevant especially in the process of professional training of applicants for higher education. Furthemore, It is very important for graduates to think independently, propose non-standard ideas, show a creative approach to various situations. It determines the direction of modern education towards the development of creativity. After all. we concluded that the development of creativity of applicants for higher education contributes to their successful employment in the future